Improving Interest and Speech Writing Skills through a Process Approach Assisted by the Learning Management System (LMS) among Grade VIII Students at Cinta Kasih Tzu Chi Cengkareng Junior High School - Theresia Niken Dwi Utami Putri; Kastam Syamsi; Ary Kristiyani (FKIP - Universitas Riau, 2026)
This research is motivated by low interest and suboptimal speech writing skills among eighth-grade students at Cinta Kasih Tzu Chi Cengkareng Junior High School, caused by conventional methods that neglect the writing process. This study aims to improve students' interest and speech writing skills through an LMS-assisted process approach. Utilizing a Classroom Action Research (CAR) design over two cycles, the study involved 32 grade VIII students. Data were collected via observations, interviews, questionnaires, written tests, and documentation, then analyzed descriptively. The results showed a significant increase in student mastery, rising from 9.375% in the pre-intervention stage to 15.625% in Cycle I, and peaking at 100% in Cycle II, with scores ranging from 75 to 95. The integration of the process approach and LMS created an interactive environment that enhanced active participation and focus. The study concludes that an LMS-assisted process approach can support the improvement of students' speech writing skills when digital learning is integrated with structured writing stages, teacher guidance, peer feedback, and revision.